Need for managerial interventions in scaling up traditional agroforestry practices: An insight - Jacob, Vinu; Bijalwan, Arvind; Verma, Pooja; Dobriyal, M.J.R. (Indian Journal of Agroforestry, 2019)
Agroforestry has gained enormous popularity and limelight in the recent decades. The synergic action of carbon sequestration and environmental resilience associated with these systems has elicited its worldwide adoption, as it's a simple yet effective elixir to the myriad of environmental and social problems faced in the present era. It's a realistic solution to the major sustainable development goals framed by United Nations where developing countries are given equal concern. To embrace these goals, it demands the sustainable intensification and commercialisation of traditional agroforestry through scientific transformation. To achieve this, managing agroforestry components like trees and crops are quintessential, thereby upgrading traditional agroforestry systems in addressing food security, rural poverty, biodiversity conservation, protecting watershed services, wood demand and resilience to climate change. Although various management practices are adopted in agroforestry systems at farmer level, there is a dearth of sufficient research back up to examine the effect of these practices. In order to address these research gaps, this paper critically discusses the various management practices which can be deliberately incorporated into traditional agroforestry systems to enhance the system productivity, concurrently uplifting thesocio-economic status of farmers ensuring nutritional security and thus empowering agroforestry systems with a much more promising future.